Multiple roles of the F-box protein Slimb in Drosophila egg chamber development. - Muzzopappa, M.; Wappner, P. (Development, 2005)
Substrate-specific degradation of proteins by the ubiquitin-proteasome pathway is a precise mechanism that controls the abundance of key cell regulators. SCF complexes are a family of E3 ubiquitin ligases that target specific proteins for destruction at the 26S-proteasome. These complexes are composed of three constant polypeptides--Skp1, Cullin1/3 and Roc1/Rbx1--and a fourth variable adapter, the F-box protein. Slimb (Slmb) is a Drosophila F-Box protein that fulfills several roles in development and cell physiology. We analyzed its participation in egg chamber development and found that slmb is required in both the follicle cells and the germline at different stages of oogenesis. We observed that in slmb somatic clones, morphogenesis of the germarium and encapsulation of the cyst were altered, giving rise to egg chambers with extra germline cells and two oocytes. Furthermore, in slmb somatic clones, we observed ectopic Fasciclin 3 expression, suggesting a delay in follicle cell differentiation, which correlated with the occurrence of ectopic polar cells, lack of interfollicular stalks and mislocalization of the oocyte. Later in oogenesis, Slmb was required in somatic cells to specify the position, size and morphology of dorsal appendages. Mild overactivation of the Dpp pathway caused similar phenotypes that could be antagonized by simultaneous overexpression of Slmb, suggesting that Slmb might normally downregulate the Dpp pathway in follicle cells. Indeed, ectopic expression of a dad-LacZ enhancer trap revealed that the Dpp pathway was upregulated in slmb somatic clones and, consistent with this, ectopic accumulation of the co-Smad protein, Medea, was recorded. By analyzing slmb germline clones, we found that loss of Slmb provoked a reduction in E2f2 and Dp levels, which correlated with misregulation of mitotic cycles during cyst formation, abnormal nurse cell endoreplication and impairment of dumping of the nurse cell content into the oocyte.